'Against Any Army': Italian Radical Party's Antimilitarism from the 1960s to the Early 1980s. (July 2021) - Bonfreschi, Lucia
This article focuses on the Italian Radical Party's (PR) antimilitarism, which combined left liberal with libertarian and anti-authoritarian elements. The aim of the paper is twofold: highlight the existence of a 'third way' of mobilisation for peace, distinct from the communist and the Catholic movements that tend to dominate the literature on Italian peace protest; and investigate peace mobilisation not only during the late 1960s or the early 1980s, but also during the 1970s, a decade neglected by historiography. In so doing, the article traces the development of the Radicals' antimilitarism from its beginning in the 1960s up to the early 1980s, with the aim of understanding the origins of their antimilitarist ideas, their political strategy, their complex mediation between movements and institutions and their efforts to institutionalise antimilitarist issues.